Analisis Implementasi Aplikasi Accurate Pada PT MCG - Dinny Irfani; Irawan Irawan; Nurmala Nurmala (Politeknik Negeri Lampung, 2018)
The purpose of this final report is to analyze the implementation of Accurate application on PT MCG. The data used include the reports produced by the Accurate application that is the income statement of PT MCG, and the output produced by Accurate application. The author uses qualitative methods to provide information about the menus contained in the application Accurate, and the menus in the application Accurate used PT MCG and its function for PT MCG. The Accurate application on PT MCG has deficiencies in the resulting financial reports. The Accurate application used by PT MCG only results in the income statement. The resulting profit and loss statement has not complied with the applicable regulations, since the income statement of PT MCG does not represent costs as one of the components of the income statement of the company. The use of Accurate application on PT MCG has not been optimal in the preparation of the company's financial statements in particular can not display the statement of financial position (balance sheet). The authors suggest that companies use the more comprehensive new version of the Accurate versiter application. Keywords: Accurate, Income Statement, PT MCG.